Nanoemulsion as Novel Drug Delivery System: Development, Characterization and Application - Dhumal, Nikhil; Yadav, Vishal; Borkar, Smita (Asian Journal of Pharmaceutical Research and Development, 2022)
A dispersed nano-system with droplet sizes as small as submicrons is called a nanoemulsion. Nanoemulsions are thermodynamically stable, transparent, isotropic liquid mixtures of oil, water, surfactant, and co-surfactant. Nanoemulsion typically has droplet sizes between 20 and 200 nanometer. The size and composition of the scattered particles in a continuous phase are the primary distinctions between an emulsion and a nanoemulsion. This approach is intended to alleviate some of the issues that low bioavailability and noncompliance, two issues with traditional drug delivery systems, bring up.Today, nano emulsion can be created for a number of administration routes. A nano emulsion formulation can be considered an effective, secure, and patient-compliant pharmaceutical delivery method. Nowadays, nano emulsions have attracted a lot of interest in pharmacotherapy, dosage form design, and research. A surfactant and a cosurfactant can preserves the stability components of nanoemulsion. Brief details on the types, preparation process, stability, assessment, and applications of nanoemulsion are provided in this review.